KEMANDIRIAN BELAJAR DITINJAU DARI KREATIVITAS BELAJAR DAN KEIKUTSERTAAN SISWA DALAM ORGANISASI SEKOLAH PADA SISWA KELAS VII DAN VIII SMP NEGERI 2 KEDUNGJATI GROBOGAN TAHUN AJARAN 2014/2015 - Fatharlino, Hegar, Drs. M. Yahya, M.Si (2015)
Hegar Fatharlino, A210110078. Essay. Accounting Education Studies Program, the Faculty of Education, University of Muhammadiyah Surakarta. August 21, 2015 The purpose of this study was to determine: 1) the influence of the independent learning creativity studying in Class VII and VIII OSIS committee SMP Negeri 2 Kedungjati Grobogan 2014/2015 school year, 2) the influence of student participation in school organization for independent learning in class VII and OSIS committee VIII SMP Negeri 2 Kedungjati Grobogan academic year 2014/2015, 3) influence learning creativity and keikitsertaan students in the school organization in class VII and VIII OSIS committee SMP Negeri 2 Kedungjati Grobogan the academic year 2014/2015. The population in this study were students of class VII and VIII which follows the organization of the school SMP Negeri 2 Kedungjati Grobogan the academic year 2014/2015. This research method is quantitative research associative. The sampling technique using probability sampling techniques incidental. Data collection techniques using methods Questionnaire. The analysis prerequisite test used normality test, linearity test, test multiple linear regression analysis. Data were analyzed using t-test, F, and the relative contribution and effective. Results of regression analysis to obtain the regression line equation: Y = X1 + 0.185 9,280+ 0,116X2. The equation shows that independent learning is influenced by the creativity of learning and participation of students in the school organization. The conclusions drawn are: 1) There is the influence of learning creativity tehadap independent learning in class VII and VIII OSIS committee SMP Negeri 2 Kedungjati, obtained by t test, t count> t table = 2.923> 2.021 and the significance value of 0.05, which is 0.006, 2 ) There is the influence of student participation in school organization for independent learning in class VII and VIII OSIS committee SMP Negeri 2 Kedungjati Based on t test was obtained, t count> t table = 2.549> 2.021 and the significance value of 0.05, which is 0.015, 3) There is an effect of creativity learning and participation of students in the organization sekolahpada class VII and VIII OSIS committee SMP Negeri 2 Kedungjati. Based on F test obtained value of F count> F table = 9.561> 3.23 4) Variable creativity learning contribute effectively amounted to 18.97%, the variable student participation in school organizations contribute effectively amounted to 15.13% 5) Variable learning creativity to contribute relatively amounted to 55.65%, the variable student participation in school organizations providing relative contribution of 44.35%. Keywords: Creativity Learning, Student Participation in School Organization, Independence Learning